Farmers’ Capacity for Jatiluwih Agrotourism Management and Its Effects on Tourists’ Satisfaction and Intention to Revisit - Patricia, Tien Cathy; Suryawardani, I Gusti Ayu Oka; Suamba, I Ketut; Wiranatha, Agung Suryawan (E-Journal of Tourism; Volume 7 Number 1 (March 2020), 2020)
Capacity is the main element for farmers in achieving their goals. Farmer’s Capacity consists elements of knowledge, attitude, and skills. With the increasing number of visits in Bali, especially Jatiluwih Agrotourism, farmers should be the subject of management so that they can fully enjoy the benefits of the visit. With the existence of agrotourism, agriculture and tourism can be a pair of harmonious sectors. Tourist’s feedback on the satisfaction and intention to revisit can be an input in the effort to increasing the farmer’s capacity in agrotourism management for its sustainability. This paper analyzes Farmer’s Capacity for Jatiluwih Agrotourism Management and Its Influence toward Tourist’s Satisfaction and Intention to Revisit. Primary and secondary data were obtained through interviews and filling out questionnaires with the Structural Equation Modeling (SEM) analysis method. The results of Partial Least Square (PLS) analysis show that farmer’s capacity has a significant effect on tourists’s satisfaction, which leads to tourists’s intention to revisit. it is expected that higher capacity of agroutourism management among farmers will increase tourist’s satisfaction which affects tourist’s intention to revisit hence, improving the welfare of the community, especially farmers in Jatiluwih Agrotourism. Keywords: Farmers’ Capacity, Satisfaction, Revisit, PLS